CULTIVATING RELIGIOUS MODERATION THROUGH THE PANCASILA STUDENT PROFILE AND RAHMATAN LIL 'ALAMIN AT THE TSANAWIYAH MADRASAH LEVEL - Sarnoto, Ahmad Zain; Hude, Darwis; Susanto, Susanto (Sekolah Tinggi Agama Islam Al Hidayah, 2025)
Background: Indonesia is a country with a diversity of people in various aspects, such as ethnicity, customs, culture, and religion. Objective: This study aims to analyze the instillation of religious moderation values in the development of the Pancasila Student Profile in the environment of Madrasah Tsanawiyah, using the concept of rahmatan lil alamin as its foundation. Method: This research uses a qualitative approach through literature studies to explore information related to the instillation of religious moderation values in the project to strengthen the Pancasila Student Profile and rahmatan lil ‘alamin at the Madrasah Tsanawiyah level. Research data were obtained from various sources, such as books, scientific articles, and relevant research reports. Results: Based on the research findings, the project to strengthen the Pancasila Student Profile has proven effective in fostering values of tolerance, appreciation of diversity, and awareness of the importance of harmonious coexistence. The concept of rahmatan lil alamin is also applied through various activities that prioritize love, care, and social justice. Conclusion: Thus, the implementation of the values of religious moderation through these two projects is expected to shape students' character to be moderate, tolerant, and highly upright, in accordance with the goals of national education.